Rapid quantitation by PCR of endomycorrhizal fungi colonizing roots. - Simon, L; Lévesque, R C; Lalonde, M (Genome Research, 1992)
The VANS1/NS21 primer pair is useful for specifically amplifying a 550-bp ribosomal (r) DNA fragment from arbuscular endomycorrhizal fungi, directly from colonized root extracts. A procedure to quantitate these obligatory biotrophs rapidly, based on competitive PCR, was developed by constructing a suitable internal standard to be used with these primers. A 130-bp deletion in the Glomus mossae VANS1/NS21 amplified rDNA fragment was produced by amplifying separately external portions of that fragment, followed by ligation and amplification using the original external primers. When this deleted fragment was added to G. mossae rDNA, amplification using VANS1/NS21 primers yielded the two expected products of 430 bp and 550 bp, respectively, resolved by agarose electrophoresis. This fragment was cloned into the pCL1920 plasmid, a low-copy-number vector (five copies per cell), and mixed with the roots to be analyzed. This provides for a rapid quantitative assay because both steps--extraction of DNA from colonized roots and PCR amplification--are taken into account by the same internal standard. Using this procedure, a sample of colonized leek roots (Allium porum x Glomus vesiculiferum) was shown to contain 5 x 10(4) copies of arbuscular endomycorrhizal fungi rDNA genes per milligram of fresh weight.
10.1101/gr.2.1.76